ANTIOXIDANT ACTIVITIES OF CURCUMIN TO MDA BLOOD SERUM CONCENTRATION AND LEAD LEVELS IN LIVER OF MICE - S., Sugiharto; Darmanto, Win; Wahyuningsih, Sri Puji Astuti; Hayati, Alfiah; Martha, Yani; Olivia, Putri; Putri, Kevita (Malaysian Journal of Science, 2019)
Human and animals can accidentally be exposed to heavy metals from the environment such as lead (Pb). Lead may induce oxidative stress. It can increase the production of free radicals, and induces several responses in physiological and biochemical functions of the body. Curcumin, a major component of turmeric, is commonly used as a spice and in traditional medicine. The objective of this research was to evaluate the antioxidant activities of curcumin in mice that were exposed to lead. Research was conducted using twenty five male mice, which were grouped into five treatments: P1 (control), P2 (Pb 75 mg/kg BW), P3 (Pb 150 mg/kg BW), P4 (Pb 75 mg/kg BW + curcumin 20 ppm), P5 (Pb 150 mg/kg BW + curcumin 20 ppm). The results showed that antioxidant activities of curcumin was very strong with an IC-50 was 9.0 ppm. Pb exposure increased MDA level (17.143–17.891 µM) and Pb level in the liver (0.070–0.071 mg/kg BW). Administration of curcumin 20 ppm have the potential to reduced MDA level (14.592–15.714 µM) and reduce Pb levels (0.035–0.038 mg/kg BW).